Analysis of The Influence of Effective Teaching Methodology, Knowledge of Curriculum Design and Class Mastery on The Effectiveness of Teaching and Learning Activities - Hadi Prayitno; Ilmi Noor Rahmad; Cahya Amalia Chusna; Saryanto Saryanto; Vandan Wiliyanti (Departement of Mathematics Education, 2024)
This study aims to analyze the role of teaching methodology and performance in teacher training. The researcher used the document analysis method. This study involved 100 teachers. The results of the study concluded that the balance between academic standards and the diversity of students' intellectuality needs to be considered, this can create holistic and contextual learning. Teachers need to have comprehensive knowledge and skills in subject matter, teaching methodology, and readiness to adapt to student needs and learning contexts. Thus, education is not only about teaching materials but also about time management, creating student enthusiasm and motivation, and adjusting teaching methods. To ensure that all students can understand and master the material, teachers must prepare thoroughly and continuously.